2021
DOI: 10.3390/toxins13050329
|View full text |Cite
|
Sign up to set email alerts
|

Charged Residues Flanking the Transmembrane Domain of Two Related Toxin–Antitoxin System Toxins Affect Host Response

Abstract: A majority of toxins produced by type I toxin–antitoxin (TA-1) systems are small membrane-localized proteins that were initially proposed to kill cells by forming non-specific pores in the cytoplasmic membrane. The examination of the effects of numerous TA-1 systems indicates that this is not the mechanism of action of many of these proteins. Enterococcus faecalis produces two toxins of the Fst/Ldr family, one encoded on pheromone-responsive conjugative plasmids (FstpAD1) and the other on the chromosome, FstEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The origin and function of the parEF0409 TA-1 system remains unclear, but several pieces of circumstantial evidence suggest that its function may be coordinated with that of surrounding genes. First, as previously reported (33), mutation of an efflux pump located two Kbp downstream of mtlD results in hypersensitivity to FstEF0409, the parEF0409 toxin. Located between the mtlA2 operon and the genes for the efflux system are genes annotated as NAD binding proteins that could conceivably be involved in recycling the NAD+ cofactor required for MtlD function.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The origin and function of the parEF0409 TA-1 system remains unclear, but several pieces of circumstantial evidence suggest that its function may be coordinated with that of surrounding genes. First, as previously reported (33), mutation of an efflux pump located two Kbp downstream of mtlD results in hypersensitivity to FstEF0409, the parEF0409 toxin. Located between the mtlA2 operon and the genes for the efflux system are genes annotated as NAD binding proteins that could conceivably be involved in recycling the NAD+ cofactor required for MtlD function.…”
Section: Discussionmentioning
confidence: 73%
“…In-frame, markerless deletions of mltA, mtlR, mtlF and mltA2 were constructed in OG1RF by allelic exchange using vector pJH086 (39) as previously described (33, 40). The mutant alleles were synthesized by Blue Heron Biotech, LLC, (Bothell, WA, USA) and contained the first 5 and last 5 codons of the corresponding gene and approximately 900 base pairs of flanking DNA.…”
Section: Methodsmentioning
confidence: 99%
“…For some type I toxins, charged residues are critical for their toxicity and/or formation of larger complexes [ 23 , 31 , 32 ]. We thus examined the contribution of charged residues in ZorO activity by generating the specific point mutations ( Table S3 ) and monitoring the effects after overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…Single amino acid substitutions or multiple deletion/truncation studies of type I toxins from both Gram-positive and Gram-negative bacteria have shown stretch of hydrophobic residues to be critical [ 24 , 35 ]. In the Fst type I toxin, the charged residues of the C-terminal tail are important for maximal function of the toxin [ 23 ]. In ZorO, two charged residues, glutamate at the 16th position and arginine at the 23rd position, are consistently predicted to be in the transmembrane domain regardless of the in silico approach used ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation